tính (3+1)(32+1)...(364+1)+1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(3-1\right)A=\left(3-1\right)\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\\ 2A=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\\ 2A=\left(3^4-1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\\ 2A=\left(3^8-1\right)\left(3^8+1\right)...\left(3^{64}-1\right)\\ ...\\ 2A=\left(3^{64}-1\right)\left(3^{64}+1\right)\\ 2A=3^{128}-1\)
Vậy \(A=\dfrac{3^{128}-1}{2}.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Rút gọn: (3 + 1)(3^2 + 1)(3^4 + 1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
A=(3 + 1)(3^2 + 1)(3^4 + 1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
2A=2(3 + 1)(3^2 + 1)(3^4 + 1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
2A=(3-1)(3 + 1)(3^2 + 1)(3^4 + 1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
2A=(3^2-1)(3^2 + 1)(3^4 + 1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
2A=(3^4-1)(3^4 + 1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
2A=(3^8-1)(3^8 + 1)(3^16 + 1)(3^32 + 1)
2A=(3^16-1)(3^16 + 1)(3^32 + 1)
2A=(3^32 - 1)(3^32 + 1)
2A=3^64-1
=>A=(3^64-1) /2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(12000+X):376=X
12000+X=376 x X
12000=376 x X - X
12000=375 x X
X=12000:375= 32
![](https://rs.olm.vn/images/avt/0.png?1311)
13.8.250=13.(8.250)=13.1000=13000
364-(364-111)=(364-364)+111=0+111=111
1+2+3+...+1500=(1+1500).1500:2=1125750
a, 13 x 8 x 250
= 250 x 8 x 13
=2000 x 13
=26000
còn lại tự làm nha
![](https://rs.olm.vn/images/avt/0.png?1311)
`A=4(3^2+1)(3^4+1)...(3^64+1)`
`=>2A=(3^2-1)(3^2+1)(3^4+1)...(3^64+1)`
- Ta có:
`(3^2-1)(3^2+1)=3^4-1`
`(3^4-1)(3^4+1)=3^16-1`
`....`
`(3^64-1)(3^64+1)=3^128-1`
Suy ra `2A=3^128-1=B`
`=>A<B`
![](https://rs.olm.vn/images/avt/0.png?1311)
819 + 364 + 181 + 636 - 636 - 364 - 100 + 32 : 4
= 819 + 181 + 364 - 364 + 636 - 636 - 100 + 8
= 1000 + 0 + 0 - 100 + 8
= 1000 - 100 + 8
= 900 + 8
= 908
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 364 - ( 364 - 111 )
= ( 364 - 364 ) + 111
= 0 + 111
= 111
b, 249 - ( 75 - 51 )
= ( 249 + 51 ) - 75
= 300 - 75
= 225
1, Tính nhanh
a,364-(364-111)
- 364 - 364 + 111
- 0 + 111
- 111
b,249-(75-51)
- 249 - 75 - 51
- ( 249 + 51 ) -75
- 300 - 75
- 225
c,100+98+96+..+2-97-95-...-1
- = 100 + ( 98 - 97 ) + ( 96 - 95 ) + ...+ ( 2-1)
- = 100 + 1+1+...1
- = 100 + 1.49
- = 100 + 49
- = 149
Đặt A = ( 3 + 1 )( 32 + 1 )...( 364 + 1 ) + 1
=> 2A = 2( 3 + 1 )( 32 + 1 )...( 364 + 1 ) + 2
= ( 3 - 1 )( 3 + 1 )( 32 + 1 )...( 364 + 1 ) + 2
= ( 32 - 1 )( 32 + 1 )...( 364 + 1 ) + 2
= ( 364 - 1 )( 364 + 1 ) + 2
= 3128 - 1 + 2 = 3128 + 1
=> A = ( 3128 + 1 )/2